Programa “Mundo Ecológico” para mejorar la conciencia ambiental en los estudiantes de primer grado de educación primaria, Trujillo, 2019 - Llempen Camacho, Shirley Lisset (2021)
The objective of this research work was to determine the influence of the “Ecological World” Program in the improvement of environmental awareness in the primary education students of the Educational Institution No. 81017 “Santa Edelmira”, Trujillo, 2019. They were registered with a sample of 61 students, 34 from the control group and 27 from the experimental group. The instrument was considered: “Questionnaire to measure the level of environmental awareness in first grade primary school students”, which was once a content validity by Expert Judgment and Cronbach Alpha reliability with an acceptable level of reliability (0, 89427). The constant program of 16 workshops which were applied in approximately three months. The results of the research that the “Ecological World” program has managed to improve environmental awareness by 90% were applied the Whitney U Mann non-parametric test for independent samples with a significance level of less than 5% (p <0.05).